Comparison of antimicrobial and thrombolytic central venous catheter lock solutions in preventing catheter-related complications in hemodialysis: a randomized controlled trial - Azaševac, Tijana; Stražmešter Majstorović, Gordana; Ljubičić, Bojana; Djurović, Vladimir; Knežević, Milica; Marković, Mira (Vojnosanitetski pregled, 2026)
Background/Aim. Central venous catheters (CVC) in hemodialysis (HD) patients are associated with serious complications, particularly catheter-related bloodstream infection (CRBSI) and thrombosis, leading to increased morbidity and mortality. The aim of this study was to evaluate the effectiveness of three different catheter lock solutions in preventing major catheter-related complications. Methods. This prospective, randomized, controlled, single-center study, conducted between June 2018 and June 2023, included 96 adult HD patients. Depending on the solutions they received, the patients were equally divided into three groups: gentamicin-citrate twice weekly plus taurolidine/urokinase after the third weekly session (TAURO); gentamicin-citrate three times weekly (GENTAM); unfractionated heparin 5,000 international units/mL three times weekly (HEPARIN). Lock solutions were administered for a minimum of three months post-CVC insertion and continued until catheter removal. Measured outcomes included CRBSI incidence, catheter thrombosis, and adverse events. Results. Over the course of 10,770 catheter-days, eight CRBSI episodes were recorded, with Staphylococcus aureus as the most common pathogen (50%). The incidence of CRBSI (per 1,000 catheter-days) was 0.27 in the TAURO group, 0.83 in the GENTAM group, and 1.15 in the HEPARIN group, without statistical significance (p = 0.526). Thrombosis incidence was similar across groups (1.09–1.15; p = 0.990). Cox proportional hazards analysis revealed no significant differences, although the TAURO group demonstrated a trend toward lower CRBSI risk compared to the HEPARIN group (hazard ratio = 0.236; 95% confidence interval 0.026–2.116). Conclusion. None of the evaluated lock regimens significantly reduced the risk of CRBSI or thrombosis. Nonetheless, the lowest CRBSI incidence was observed in the TAURO group, suggesting a potential benefit that warrants confirmation in larger, multicenter studies.
Keywords: anticoagulants; bacteremia; catheter-related infections; catheterization, central venous; fibrinolytic agents; renal dialysis; thrombosis.